INFORMATION TECHNOLOGY FOR DIAGNOSING THE STATE OF THE HUMAN CARDIOVASCULAR SYSTEM - LEHENCHUK, SERHII; KOVBASIUK, SERHII; MORGUN, ANASTASIIA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Modern systems designed for monitoring various aspects of human health provide valuable data and information for both individuals and medical professionals. Among their important objectives are monitoring personal health, managing the treatment process, tracking the history of disease development, remote patient monitoring, early detection, and prevention, among others. Health monitoring systems allow individuals to track and control their health parameters, such as heart rate, blood pressure, sleep patterns, level of physical activity, etc. This helps in better understanding one’s overall well-being and making informed decisions about lifestyle and habits. However, each existing system has its advantages and disadvantages. Since a suitable application was not found, a decision was made to design and develop my own information technology for diagnosing the state of the human cardiovascular system. This paper established the main tasks for the development of a web application, analyzed analogs of the developed system, determined the main functionality and requirements for the system. A methodology for assessing the state of the human cardiovascular system was selected, technologies for developing the web application were chosen, and the system’s working algorithms and object-oriented structure were designed and implemented. The software product was tested for functionality. Simplicity and ease of use were requirements during the development. The web application is intended for controlling the state of the cardiovascular system and for preventing the risk of diseases, as timely identification of problems can allow for treatment with medication therapy. Self-diagnosis applications are the first step towards diagnosing a disease or making an initial health assessment, a much better option than searching for information on the internet. While they are not yet able to replace a professional medical examination, they can be excellent advisors.
Keywords: information technology; cardiovascular system; diagnostics; SCORE; Systematic Coronary Risk Evaluation; blood pressure; diseases; medical information systems